Microemulsion Delivery System Improves Cellular Uptake of Genipin and Its Protective Effect against Aβ1-42-Induced PC12 Cell Cytotoxicity - Yujie Zheng; Guangzhi Xu; Qinxue Ni; Yan Wang; Qianxin Gao; Youzuo Zhang (MDPI AG, 2022)
Genipin has attracted much attention for its hepatoprotective, anti-inflammatory, and neuroprotection activities. However, poor water solubility and active chemical properties limit its application in food and pharmaceutical industries. This article aimed to develop a lipid-based microemulsion delivery system to improve the stability and bioavailability of genipin. The excipients for a genipin microemulsion (GME) preparation were screened and a pseudo-ternary phase diagram was established. The droplet size (DS), zeta potential (ZP), polydispersity index (PDI), physical and simulated gastrointestinal digestion stability, and in vitro drug release properties were characterized. Finally, the effect of the microemulsion on its cellular uptake by Caco-2 cells and the protective effect on PC12 cells were investigated. The prepared GME had a transparent appearance with a DS of 16.17 ± 0.27 nm, ZP of −8.11 ± 0.77 mV, and PDI of 0.183 ± 0.013. It exhibited good temperature, pH, ionic strength, and simulated gastrointestinal digestion stability. The in vitro release and cellular uptake data showed that the GME had a lower release rate and better bioavailability compared with that of free genipin. Interestingly, the GME showed a significantly better protective effect against amyloid-β (Aβ1-42)-induced PC12 cell cytotoxicity than that of the unencapsulated genipin. These findings suggest that the lipid-based microemulsion delivery system could serve as a promising approach to improve the application of genipin.